Media and Health Information Literacy among Senior Citizens in Iceland - Ágústa Pálsdóttir (Revista Română de Biblioteconomie și Știința Informării = Romanian Journal of Library and Information Science, 2017)
Competency in media and health information literacy (MHIL) is important as a tool for lifelong learning, which provides people with opportunities to make informed decisions about healthy living. In order to improve knowledge about how senior citizens lifelong learning can be supported, the study investigated various aspects of MHIL among seniors: motivation, information seeking behaviour and evaluation of information in the Media, from Health specialists and on the Internet. A random sample was used and data collected in 2012. Participants were categorized into two groups, 60 to 67 years and 68 years or older. Data analysis was performed with ANOVA (one-way). The findings suggest that the age groups have more in common than what differentiates them. They are equally motivated, have the same preferences for information seeking and information channels, and hold the same beliefs about information quality. The main differences were that the younger group sought information somewhat more frequently, and the older group was more critical of information quality.